The Changing Face of Emergency General Surgery: A 20-year Analysis of Secular Trends in Demographics, Diagnoses, Operations, and Outcomes. Issue 3 (March 2020) - Wohlgemut, Jared M.; Ramsay, George; Jansen, Jan O.
Abstract : Objective: The aim of the study was to evaluate secular trends in the epidemiology of emergency general surgery (EGS), by analyzing changes in demographics, diagnoses, operations, and outcomes between 1997 and 2016. Summary Background Data: The provision and delivery of EGS services is a globally and regionally important issue. The impact of changing demographics and surgical disease incidence on EGS services is not well understood. Methods: Data from all EGS hospital episodes of adults (aged >15) in Scotland between 1997 and 2016 were prospectively collected, including ICD-10 diagnostic codes and OPCS-4 procedure codes. The number and age- and sex-standardized rates per 100, 000 population, per year, of the most common diagnoses and operations were calculated. We analyzed demographic changes over time using linear regression, and changes in characteristics, diagnoses, operations, and outcomes using Poisson analysis. Results: Data included 1, 484, 116 EGS hospital episodes. The number and age- and sex-standardized rate, per 100, 000 population, of EGS admissions have increased over time, whereas that of EGS operations have decreased over time. Male admissions were unchanged, but with fewer operations over time, whereas female admissions increased significantly over time with no change in the operation rate. Poisson analysis demonstrated secular trends in demographics, admissions, operations, and outcomes in depth. Conclusions: This 20-year epidemiological study of all EGS hospital episodes in Scotland has enhanced our understanding of secular trends of EGS, including demographics, diagnoses, operations, and outcomes. These data will help inform stakeholders in EGS service planning and delivery, as well as in surgical training, what has occurred in recent history.